Supporting Remote Laboratory Activities at an Institutional Level - Kist, Alexander A.; Gibbings, Peter; Maxwell, Andrew D.; Jolly, Hannah (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Learning Tools that rely on information and communication technologies form an essential part of distance education. Remote Access Laboratories (RAL) is one example that has been widely discussed in the research community; in particular, in the context of engineering and science education. However, remote laboratory technology is not widely used. This study explores whether the benefits offered by the RAL systems can be extended to students in other disciplines and how this process can be supported. The key aim of this activity is to create more equitable opportunities for student learning across faculties and the university. The study identifies considerations for the wider adoption, implementation and uptake of remote laboratory based learning activities. Four learning activities at various stages of the development cycle in three different disciplines are evaluated using a program logic methodology. Evaluation questions address the areas of appropriateness, effectiveness, efficiency, impact and sustainability. It is concluded that remote laboratory are open and flexible enough to suite a variety of learning objectives and pedagogies in a number of contexts. This study also highlights some wider issues that are significant to the acceptance of RAL learning activities. Findings include that a number of conditions need to be met if remote laboratory activities are to occur more broadly across universities as learning systems.